PERENCANAAN KEUANGAN SYARIAH BAGI KELUARGA PADA DESA PAMIJAHAN, KECAMATAN PAMIJAHAN, KABUPATEN BOGOR - Trihantana, Rully; Rizal, Muhammad; Sari, Restia Rahma (Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah: Program Studi Perbankan Syariah., 2024)
Family financial planning as a systematic, comprehensive and planned process for identifying and analyzing one's investment needs and goals to achieve family financial goals, this is very important for achieving family welfare. Basic Islamic values ​​are needed as a guide in family financial planning. This community service program aims to socialize sharia economics in family financial management as an effort to improve household financial planning, by taking lessons from learning in the village of Pamijahan. The result of this activity shows the enthusiasm to immediately implement sharia family financial planning